Bean production practices and bottlenecks among smallholder farmers in Malawi - National Bean Programme (National Bean Programme, 1990)
Three hundred small farmers from 42 villages of 5 Malawian regions were interviewed in order to gather information on the most common bean cropping systems, socioeconomic structure, farmers'organizations and income-generating activities, and extension service. Common beans are the 2nd most important crop after maize, providing a cheap source of protein for the majority of people in the country. The av. no. of var. grown/farm is 2.17. Data are given on the reasons for preferring some var., the forms in which beans are sold and consumed, and the preference percentage of the 4 most commonly grown var. (Chimbamba, Kaulesi, Nanyati, and Kayera). (CIAT)